The strategic importance of new silk road in the context of Turkish, American and Russian foreign policy perpective - BALCI, MERAL (Al Farabi Kazakh National University, 2018)
It can be seen that the roads that play an important role in conveying the ideas of humanity, as well as the knowledge, the values and the beliefs, also have a special position in international relations. This way, the use of geopolitical power over geography is achieved via the control of environmental factors through people. The Silk Road, the first and the most important intercontinental trade route, is a general name given to trade routes that start from China, go through Anatolia and the Mediterranean, and end in Europe. The route which gets its name from one the most precious commodities of the time, silk, has also enabled intercultural interaction and the exchange of ideas. Even though the Silk Road had lost its importance with the discovery of alternative routes, it has become one of the key issues in international relations in recent times. China's geopolitical importance has grown immensely with the fastfinancial development and economic growth of China beginning from the 2000s. China is taking important steps in the name of the New Silk Road Project, also known as the "One Belt One Road Initiative," which is considered to be the largest transportation project in the world. The countries that the historical Silk Road passes through are making an effort to make the New Silk Road stronger than before. With China leading the project, this project closely concerns Turkey and Russia, along with the former Soviet Central Asian Republics that gained their independence after the dissolution of the Soviet Union and who are now trying to be integrated into the world economy. The new prospective route that will be built will represent the economic belt that will connect China, Central Asia, Russia and Europe by land. Also, railways, airports, ports and new energy routes will be constructed rapidly with the development of the project's infrastructure. The New Silk Road Project is aimed to connect 65 countries in total via sea, air and land routes. The project will approximately cost 21 trillion dollars. A project like this involving China and Russia creates a threat to the national interests of the United States and its Asia-Pacific policies.